Monaro dieback: simple answers are too simple. Issue 2 (3rd April 2017) - Ross, C.; Brack, C.
ABSTRACT: Ross and Brack (2015) reported the first formal survey of dieback of Eucalyptus viminalis occurring across the Monaro Plains of south-eastern New South Wales (NSW). The survey found that the dieback covered about 2000 km 2 of public and private land, and that there was no significant correlation between the observed dieback and any of the environmental or management parameters studied. Jurskis (2016) claims that the dieback in the Monaro is 'not difficult to explain', as it is simply due to the absence of grazing or regular light fire. We argue that this hypothesis cannot explain the 'Monaro dieback', and further research is required to determine the underlying cause/s. Since publication of the original survey, the authors have received a wide range of reports from academic and general observers about dieback of various species in various environments across the country. Recent observations now suggest that the 'Monaro' dieback has extended beyond the original boundary and into other Eucalyptus species. We emphasise the need for an agency or organisation to act as a central collection point for geographically referenced and time-stamped photographs or descriptions from the public in order to better monitor tree health across the country.